If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -4(2x + 3y) = 0 12 + (2x * -4 + 3y * -4) = 0 12 + (-8x + -12y) = 0 Solving 12 + -8x + -12y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -8x + -12 + -12y = 0 + -12 Reorder the terms: 12 + -12 + -8x + -12y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -8x + -12y = 0 + -12 -8x + -12y = 0 + -12 Combine like terms: 0 + -12 = -12 -8x + -12y = -12 Add '12y' to each side of the equation. -8x + -12y + 12y = -12 + 12y Combine like terms: -12y + 12y = 0 -8x + 0 = -12 + 12y -8x = -12 + 12y Divide each side by '-8'. x = 1.5 + -1.5y Simplifying x = 1.5 + -1.5y
| 6/d=3 | | 8v-5+1=-4 | | 240-83x=541 | | 3x+41-5x=3-8x+2 | | 1/4x+1/4x=8 | | k+4(2k-7)=-100 | | (3/4)/(5/7) | | 2-5p-3p=-6 | | 3/4/5/7 | | -2m-24=0 | | 2-5p-4p=-6 | | 48/60 | | y+1=6/5x+18/5 | | a+4+2a=-8 | | -8n+-4=-28 | | (-3)*(-13)+(-41)= | | -11+2(x-3)+x=3(x-3)-8 | | 1=2+1/2 | | 5(3x+2)=2(2x+3) | | 5(x-2)-3=2x+3(-3+x) | | -5(7+7n)=-280 | | x/2+6=3x-12+x/2 | | 12x+15=-2 | | 3x+7=6x+9 | | 8n-4=-28 | | -6x-2x=-8 | | Y-2=4/9(x-3) | | 5x+5+1=-9 | | b+7+6=19 | | 5/6-1/3=-2 | | 3x+4x=12+16 | | -3x+5=6x+24 |